Conservative Management of Chest Tube and Ambulatory Water Sealed Drainage in Persistent Pneumothorax due to Tuberculosis - Ni Wayan Candrawati; Franciscus Sanjaya; Irmi Syafa'ah (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Pneumothorax is characterized by the presence of air in the pleural cavity, which can result from various pulmonary conditions, including tuberculosis (TB). Conservative management, including the use of chest tubes with ambulatory water-sealed drainage (WSD), offers a viable alternative for patients who are ineligible for surgery or decline surgical intervention. This case report aimed to highlight that all treatment options should be discussed with the patient to determine their primary priority, with consideration for the least invasive option. Case: A 22-year-old woman with secondary spontaneous pneumothorax due to TB presented with shortness of breath following a cough and was found to have a >2cm lucent area on chest X-ray. Initial management included chest tube insertion and WSD. A persistent pneumothorax was identified after 13 days of admission, and surgery was advised, but the patient declined. Conservative management was continued with ambulatory drainage for a total of 34 days, and management of TB as an underlying disease, and adequate nutritional support. Over the course of a month, clinical symptoms improved, and subsequent evaluations confirmed resolution of the pneumothorax. The chest tube was removed. The patient completed 12 months of anti-TB therapy, was declared cured, and experienced no recurrence of pneumothorax. Conservative management, including ambulatory WSD, effectively manages persistent air leak (PAL) for patients unsuitable for surgery. Ambulatory WSD facilitates mobility, reduces hospital stay, and minimizes complications. Proper patient education, nutritional support, and management of underlying conditions are essential for favorable outcomes. Conclusion: The management of persistent pneumothorax should be guided by the patient’s clinical condition. Conservative management can yield favorable results, followed by best supportive management.